Auditoría energética en el municipio de Zamora. - Escobar Cabrera, Carlos Geovanny (2013)
The present research work was determined based on the development of energy audit which is the influence of energy carriers in the energy index, being the electricity and water the energy carriers that the Municipality of Zamora used. The main installed and powers that consume the most are: the lighting system, office automation equipment and other equipment, likewise the voltage levels are below the limits allowed by the regulations established by CONELEC, in addition, the power factor of the Institution is low with the change done to the electromagnetic ballasts to electronic ones of lamps. The lighting level in office rooms and other areas in the building are within the standards set by NEC, the saving energy chances found in the municipality building are: the lighting system and also in the office equipment. It is important to update drawings and electrical line diagrams of the Municipality, as well as establish an identification of each circuit either force or illumination of each panel and sub-panel also make the balance in the phases with the load voltage in the building, likewise it is necessary, to change the size of the conductor of the connection because it is far away from the main panel, for power saving, the configuration options that computers offer must be used, for example: suspend, hibernate or off the equipment, and, work must be done in places that take advantage of natural lighting and finally, make rational use of electrical energy.